SAK EMKM Inventory Based Accounting Implementation - Sitti Murniati; Herlina Herlina (Pusat Riset dan Inovasi Nasional, 2023)
Inventory is a useful resource in a trading organization because it is a larger asset than current assets. As a result, the majority of the company's revenue comes from the sale of inventory goods. To avoid fraud, inventory accounting management is essential. A trading company that supplies fundamental needs for consumers to implement accountable inventory management provided the data for this article. The name of the corporation UD Barokah Putra Makassar is the subject of this study. The qualitative descriptive method is used in this paper. According to the findings of this study, UD Barokah Putra Makassar has established accountability based on inventory management, but there is still room for development in terms of providing burden sharing for entering and storing items and income.